A New UK Defence Standard For Human Factors Integration (HFI). (September 2016) - Corbridge, Colin; Anthony, Mark; McNeish, David; Shaw, Gareth
The development of a new UK Defence Standard for Human Factors Integration is described. This formed one element of an extensive updating of Human Factors Integration guidance within UK MOD. The Standard is to be used for contracts between UK MOD and industry suppliers for Human Factors Integration activities - integral to the development of new and existing military systems. The extant Standard, Defence Standard 00-250 (2008), was deficient in a number of ways and was not well aligned with the evolving internal HFI guidance for MOD personnel. The new Standard, Defence Standard 00-251 (2015), is primarily a process standard. It specifies, in the form of Human Factors Process Requirements, what HFI activities must be undertaken throughout the system lifecycle to manage the human related risks in the development of new systems across the seven HFI domains. It also includes a number of candidate Human Factors User and System Requirements which can be used to specify properties of the system itself. A collaborative approach to the development of the Standard ensured relatively few changes were required, following a period of public consultation, prior to the final version of the Standard being produced.